Functional role of the glycan cluster of the human immunodeficiency virus type 1 transmembrane glycoprotein (gp41) ectodomain. - Fenouillet, E (1993)
To examine the role of the glycans of human immunodeficiency virus type 1 transmembrane glycoprotein gp41, conserved glycosylation sites within the env sequence (Asn-621, Asn-630, and Asn-642) were mutated to Gln. The mutated and control wild-type env genes were introduced into recombinant vaccinia virus and used to infect BHK-21 or CD4+ CEM cells. Mutated gp41 appeared as a 35-kDa band in a Western blot (immunoblot), and it comigrated with the deglycosylated form of wild-type gp41. Proteolytic cleavage of the recombinant wild-type and mutant forms of the gp160 envelope glycoprotein precursor was analyzed by pulse-chase experiments and enzyme-linked immunosorbent assay: gp160 synthesis was similar whether cells were infected with control or mutated env-expressing recombinant vaccinia virus, but about 10-fold less cleaved gp120 and gp41 was produced by the mutated construct than the control construct. The rates of gp120-gp41 cleavage at each of the two potential sites appeared to be comparable in the two constructs. By using a panel of antibodies specific for gp41 and gp120 epitopes, it was shown that the overall immunoreactivities of control and mutated gp41 proteins were similar but that reactivity to epitopes at the C and N termini of gp120, as present on gp160 produced by the mutated construct, was enhanced. This was no longer observed for cleaved gp120 in supernatants. Both gp120 proteins, from control and mutated env, were expressed on the cell surface under a cleaved form and could bind to membrane CD4, as determined by quantitative immunofluorescence assay. In contrast, and despite sufficient expression of env products at the cell membrane, gp41 produced by the mutated construct was unable to induce membrane fusion. Therefore, while contradictory results reported in the literature suggest that gp41 individual glycosylation sites are dispensable for the bioactivity and conformation of env products, it appears that such is not the case when the whole gp41 glycan cluster is removed.